Leveraging Social Media For Promoting Tour And Travel Businesses - Dzaky Kamaluddin, Ahnaf; Bintang Maulana, Fascho; Ikhsan Ramadhani, Muhammad (LPPM Universitas Duta Bangsa Surakarta, 2023)
In this global economy, the tour and travel business is a continuously growing industry worldwide. The public's need for various travel experiences can easily be met by tour and travel businesses. The increase in tourists also creates opportunities for tour and travel businesses to be more innovative in providing diverse travel experiences that can be tailored to the desires of tourists. With the push of globalization and technological advancements, tourists can easily access information related to tourist destinations, transportation, and accommodations. However, tour and travel businesses must continuously adapt to technological developments and the times for better travel experiences for future generations.